The extracellular polysaccharide determine the physico-chemical surface properties of Microcystis - Yang, Haijian; Wu, Denghua; Li, Hua; Hu, Chunxiang (Frontiers in Microbiology, 2023)
Microcystis possesses the capacity to form colonies and blooms in lakes and reservoirs worldwide, causing significant ecological challenges in aquatic ecosystems. However, little is known about the determining factors of physico-chemical surface properties that govern the competitive advantage of Microcystis. Here, The physico-chemical surface properties of Microcystis wesenbergii and Microcystis aeruginosa, including specific surface area (SSA), hydrophobicity, zeta potential, and functional groups were investigated. Additionally, the extracellular polysaccharide (EPS) were analyzed. Laboratory-cultured Microcystis exhibited hydrophilic, a negative zeta potential and negatively charged. Furthermore, no significant relationship was shown between these properties and the cultivation stage. M. wesenbergii exhibited low free energy of cohesion, high surface free energy, high growth rate, and high EPS content during the logarithmic phase. On the other hand, M. aeruginosa displayed lower free energy of cohesion, high surface free energy, high EPS content, and high growth rate during the stationary phase. These characteristics contribute to their respective competitive advantage. Furthermore, the relationship between EPS and surface properties was investigated. The polysaccharide component of EPS primarily influenced the SSA and total surface energy of Microcystis. Likewise, the protein component of EPS influenced hydrophobicity and surface tension. The polysaccharide composition, including glucuronic acid, xylose, and fructose, mainly influenced surface properties. Additionally, hydrophilic groups such as O–H and P–O–P played a crucial role in determining hydrophobicity in Microcystis. This study elucidates that EPS influenced the SSA, hydrophobicity, and surface free energy of Microcystis cells, which in turn impact the formation of Microcystis blooms and the collection.